StBlocks: Visual programming for data structures (2017)
The Data Structures course is common in Systems Engineering and Computer Science programs, providing a fundamental basis for professional training in these disciplines. This course presents a great pedagogical challenge, due to the high complexity in the algorithms studied and the levels of abstraction that it requires. Considering that the traditional pedagogical approach is sometimes not adequate to ease understanding of the structures covered in the course, we propose the development of DStBlocks as a playful and visual tool for the design and programming of data structures. Through this document we emphasize the context to be intervened and the problem to be solved, indicating the progress corresponding to the project. At the end we present the work which will be held in a near future, indicating how we are going to measure learning variables according to the project's objectives.